A NEW VARIETY OF CANTHIUMERA GLABRA (RUBIACEAE: VANGUERIEAE) - Ridha Mahyuni; Tatik Chikmawati; Nunik Sri Ariyanti; Anne Kusumawaty (Reinwardtia, 2022)
MAHYUNI, R., CHIKMAWATI, T., ARIYANTI, N. S. & KUSUMAWATY, A. 2022. A new variety of Canthiumera glabra (Rubiaceae: Vanguerieae). Reinwardtia 21(1): 13‒17. — Canthiumera glabra var. laxiflora (Rubiaceae: Vanguerieae), a new variety from Java and Sumatra is described. The new variety differs from the typical variety in having laxly branched inflorescences and is restricted to south Sumatra (Lampung) and southwestern Java.